When the Global Downturn Hits the Youth Bulge: Challenges and Opportunities for (Female) Youth Employment and Social Advancement - Mendoza, Ronald U (Archīum Ateneo, 2013)
Developing countries are presently experiencing or are shortly expected to see a “youth bulge” (a large number of young people in the national population) — some 71 in total and 11 in Asia alone — will face relatively greater employment and human capital investment challenges as a result of the global economic crisis and its medium term ramifications. Additionally, gender inequalities could also be exacerbated by the global crisis, increasing the risks particularly for female youth. To help address these issues and as a contribution to the policy discussions toward a more inclusive social and economic recovery from the crisis, this paper examines the extent to which countries with imminent or anticipated youth bulges, combined with historically persistent gender inequality, are likely to be impacted by the crisis. As a second contribution this paper develops a framework for understanding the risks faced by girls throughout the lifecycle, with an additional focus on intergenerational transmission of poverty.